2022
DOI: 10.3389/fpsyg.2022.1059786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity on regulatory emotional self-efficacy, resilience, and emotional intelligence of nurses during the COVID-19 pandemic

Abstract: The normalization of epidemic prevention and control has exacerbated nurses’ physical and mental stresses. The important role of physical activity in relieving nurses’ physical and mental stresses has received extensive attention from researchers in recent years. The purpose of this study was to investigate the influence of physical activity on the regulatory emotional self-efficacy, resilience, and emotional intelligence of nurses and explain their interactions. The present study adopted the cluster sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Self-efficacy, emotion regulation, physical activity participation, and psychological resilience are all linked in a detailed and organised way in studies that look at these relationships. When these studies are looked at in this way, it's easier to understand what we've found (Kim et al, 2023;Deng et al, 2023;Wu et al, 2022;Neumann et al, 2022). No matter how good an individual is at participating in physical activities or regulating their emotions, they cannot be psychologically resilient without developing good self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy, emotion regulation, physical activity participation, and psychological resilience are all linked in a detailed and organised way in studies that look at these relationships. When these studies are looked at in this way, it's easier to understand what we've found (Kim et al, 2023;Deng et al, 2023;Wu et al, 2022;Neumann et al, 2022). No matter how good an individual is at participating in physical activities or regulating their emotions, they cannot be psychologically resilient without developing good self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, participation provides methods for individuals to improve their ability to withstand stress in life, relieve interpersonal tension, and effectively improve their mental health [ 60 , 61 ]. Appropriate physical activity can also activate people’s cognition and behavior, promote their psychological balance, and strengthen their self-awareness and positive emotions [ 62 ] to help them maintain a higher level of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This intricate psychological framework encompasses personality attributes such as self-assurance, concentration, emotional regulation, positive cognitive patterns, tenacity, and the capacity for psychological recovery post-trauma ( Butt et al, 2010 ). Furthermore, heightened levels of resilience correlate with amplified positive emotions and enhanced emotional intelligence, facilitating more effective management of perceived stress ( Wu et al, 2022 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%